Evaluating microbial role in reducing N2O emission by dual isotopocule mapping following substitution of inorganic fertilizer for organic fertilizer. (1st December 2021) - Li, Yujia; Zheng, Qian; Yang, Rui; Zhuang, Shan; Lin, Wei; Li, Yuzhong
Abstract: Organic and inorganic fertilizers are major sources of N2 O emission in vegetable field and their combined applications are recommended in China. However, the microbial processes for N2 O production and consumption after combined applications of organic and inorganic fertilizers to vegetable field remain unclear making the optimal fertilization scheme less accurate. To address this issue, five substitution rates of organic fertilizer for inorganic fertilizer including 0 (0M), 20 (20M), 50 (50M), 80 (80M), and 100% (100M) and a no fertilizer control (NF) were evaluated on Chinese cabbage ( Brassica pekinensis L. var). N2 O fluxes, N2 O isotopocule ratios, Chinese cabbage yield and environmental parameters were measured. According to the revised dual isotopocule mapping of δ 18 O vs. δ 15 N SP (difference value of 15 N in N α –N β –O molecule site preference), the nitrification contribution for the 100M, 80M, 50M, 20M, 0M and NF treatments were 41, 28, 33, 34, 39, and 37%, respectively, and the extent of N2 O reduction were 74, 67, 48, 35, 11, and 78%, respectively. Such results suggest that denitrification was the major microbial process and was promoted by adding organic fertilizer. Increasing the substitution rates of organic fertilizer improved the extent of N2 O reduction and thus mitigated N2 O emission. In addition, increasing the substitution rates of organic fertilizer improved C/N ratio and N2 O isotopocule deltas, yet reduced N2 O emission, Chinese cabbage yield, and soil mineral nitrogen content. In all the evaluated substitution rates, the 20M treatment had the best performance in maintaining the Chinese cabbage yield and reducing the N2 O emission. These findings reveal that the dual double isotopocule mapping is useful for partitioning N2 O source and sink on a field scale. Adding organic fertilizer could reduce N2 O emission by enhancing N2 O reduction to N2 and the 20% substitution rate of organic fertilizer is the appropriate substitution rate. Furthermore, an optimal substitution rate of organic fertilizer should be explored between 20% and 50% in later studies. Graphical abstract: The increasing the substitution rates of organic fertilizer can improve the extent of N2 O reduction to mitigate N2 O emission, whereas this increase is not the more the better, which leaded to a significant decline in Chinese cabbage yield and mineral nitrogen contents (NH4 + and NO3 − ), of course as well as a significant rise in C/N ratio and N2 O isotopocule deltas ( δ 15 N SP and δ 18 O). Results showed that 20% substitution rate of organic fertilizer for inorganic fertilizer is the optimal substitution scheme. Image 1 Highlights: The reevaluated δ 18 O vs. δ 15 N SP mapping could obtain more precise results for partitioning N2 O source and sink. Increasing the substitution rates of organic fertilizer could promote N2 O reduction to N2 and then reduce N2 O emission. The 20% substitution rate of organic fertilizer has the best performance and is recommend to use. An optimal substitution rate of organic fertilizer still needs be explored between 20% and 50% in the future.